Pendidikan Karakter dan Memahami Nilai-Nilai Moral Pesantren Gontor Darussalam (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
Many Studies have describe the formation of characterin various educational institutions, such as schools, madrasas and Islamic boarding school, However, studiesthat perspective are still limited. This researchaimsto reveal how characterswith global insight are formed at Pondok Modern Darussalam Gontor. In this research, the data collection methods used include participant observation, in-depth interviews, and documentation studies. Participatory observation was carried out to understand the daily activities of the students in the Pondok Modern Darussalam Gontor environmet. Interviews were conducted with daily boarding school administratorsand student representatives to gain further insight into the character formation process. Meanwhile, the documentation study aims to collect data from various document relating to the activities and mechanisme of character formation in thi Islamic boarding school. The data analysis technique use in this research refersto the analysis model developed by Miles and Huberman. To unsure the validity of the data, this researchapplies the data triangulation method to increase the accuracy of the reserach result. The research result show that the character formation of student at Pondok Modern Darussalam Gontor is orriented towrds a global perpective and is based on three main prinsiple, namely integrative, comprehensive and independent (self_goverment). Based on these findings, the research recommends that the haracter formation model applied at Pondok Modern Darussalam Gontor can be adapted and applied more widely in various Islamic educational instituions.